Business modeling : a practical guide to realizing business value - Bridgeland, David Murray, 1961-; Zahavi, Ron. (Amsterdam ; Boston : Morgan Kaufmann/Elsevier, 2009)
Provides in-depth coverage of each of the four distinct business modeling disciplines, helping you master them all and understand how to effectively combine them. It shows how to develop models, and then analyze, simulate, and deploy them and details best practices for working with subject matter experts.
Why business modeling? -- Modeling fundamentals -- Business motivation models -- Business organization models -- Business process models -- Business rule models -- Creating a good model -- Model-based workshops -- Running a workshop -- Business model analysis -- Business simulation -- Executing a business model.
Includes bibliographical references (p. 377-378) and index.
oif 24/06/15
Loan
Keywords: Management -- Simulation methods